1982
DOI: 10.1055/s-0038-1657142
|View full text |Cite
|
Sign up to set email alerts
|

Increased Factor VIII Associated Activities in Cushing's Syndrome: A Probable Hypercoagulable State

Abstract: SummaryThirteen women and 2 men affected by Cushing’s syndrome were investigated. The following parameters were used: plasma and urinary cortisol levels, factor VIII assay (antigen, activity and von Willebrand factor) together with other coagulative assays.Samples were taken before surgery or before medical and/or radiation therapy and every 30–50 days after treatment and continued for 11 months. Cortisol and factor VIII were increased before treatment and decreased slowly after treatment to become normal in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(8 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…In our opinion, cholecystectomy and, subsequently, the anterior approach are mandatory when gallstones are present prior to surgery in order to prevent postoperative acute cholecystitis, a complication under steroid replacement therapy. As others [25,26], we have observed thromboembolic complications due to increased factor VIII activity in Cushing's syndrome, responsible for an hypercoagulable state. We advocate perioperative prevention by low-molecularweight heparin, but this opinion is not shared by others [7].…”
Section: Discussionsupporting
confidence: 72%
“…In our opinion, cholecystectomy and, subsequently, the anterior approach are mandatory when gallstones are present prior to surgery in order to prevent postoperative acute cholecystitis, a complication under steroid replacement therapy. As others [25,26], we have observed thromboembolic complications due to increased factor VIII activity in Cushing's syndrome, responsible for an hypercoagulable state. We advocate perioperative prevention by low-molecularweight heparin, but this opinion is not shared by others [7].…”
Section: Discussionsupporting
confidence: 72%
“…The thrombogenic potential of steroids is well described in the literature (Isacson, 1970; Jorgenson et al , 1982; Zanon et al , 1982; van Giezen & Jansen, 1992; Patrassi et al , 1992; Ozturk et al , 1994; Patrassi et al , 1995; Nowak‐Gottl et al , 1999, 2001a; Sartori et al , 1999; Athale & Chan, 2003b). Several investigators have shown that steroid therapy leads to elevation of factors VIII, von Willebrand factor (VWF), prothrombin and antithrombin, and decreases the levels of fibrinogen and plasminogen (Ozsoylu et al , 1962; Isacson, 1970; Jorgenson et al , 1982; Zanon et al , 1982; van Giezen & Jansen, 1992; Halton et al , 1992; Ozturk et al , 1994; Patrassi et al , 1995; Sartori et al , 1999). Steroid therapy has been shown to alter the VWF function as well as to induce a hypofibrinolytic state, with elevation of plasminogen activator inhibitor 1 (PAI‐1) levels, reduction of α 2 ‐macroglobin and decrease in the content of venous wall plasminogen activator.…”
Section: Discussionmentioning
confidence: 94%
“…The procoagulant factors that veterinary medical authors have investigated related to this procoagulant state include factors II, V, VII, IX, X, XII, and fibrinogen . In human HAC patients, the tendency toward hypercoagulability has been attributed to increases in factor activity for factor VIII alone, the combination of factors VIII, V, and prothrombin, factors XII, XI, IX, and VIII and increased factor VIII and von Willebrand factor (vWF) activity with abnormal vWF multimers and hyperresponsive platelet activity . Decreased function of the anticoagulant system has been attributed to a decrease in antithrombin concentrations .…”
Section: Discussionmentioning
confidence: 99%